2022
DOI: 10.4274/ejbh.galenos.2022.2022-4-3
|View full text |Cite
|
Sign up to set email alerts
|

The Senologic International Society Survey on Ductal Carcinoma <i>In Situ</i>: Present and Future

Abstract: Objective: Therapeutic management of ductal carcinoma in situ (DCIS) is heterogeneous among countries worldwide, and some treatment indications are still controversial. To investigate DCIS management in different countries; identify both consensual practices and controversial topics; and survey opinions about the future management of DCIS. Materials and Methods:The Senologic International Society network members participated to an online survey using a questionnaire, between November 2021 and February 2022.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Until recently, the delivery of boost dose to the tumour bed has been controversial, with some reports showing benefits for young women and others only for positive surgical margins [81,82]. An international survey [7] showed a great heterogeneity for boost indications: about one-third of the physicians never delivered boost and the remaining two-thirds split over delivering it always or only in the presence of risk factors.…”
Section: Tumour Bed Boostmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, the delivery of boost dose to the tumour bed has been controversial, with some reports showing benefits for young women and others only for positive surgical margins [81,82]. An international survey [7] showed a great heterogeneity for boost indications: about one-third of the physicians never delivered boost and the remaining two-thirds split over delivering it always or only in the presence of risk factors.…”
Section: Tumour Bed Boostmentioning
confidence: 99%
“…The survey by Mathelin et al [7] showed that 73% of the physicians are in favour of some kind of therapy de-escalation (surgery or RT) for selected low-risk DCIS, especially for elderly women.…”
Section: Omission Of Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation